Studies on cross compatibility in Jasminum spp. - S, PAVITHRA; V, DHANANJAYA M; NAIR, SUJATHA A; KUMAR, Rajiv; S, YOGEESHA H; M, MUNIKRISHNAPPA P; V, DEVAPPA; K, HALESH G; A, KALAIYARASI (The Indian Journal of Agricultural Sciences, 2019)
The present investigation was carried out to study the compatibility among six Jasminum species during 2016–17. Among open, self and artificial cross pollination, the open pollination resulted in maximum degree of fruit and seed set proving the open pollination to be the best method of pollination. The best time for pollination was the time of anthesis. The species Jasminum malabaricum and Jasminum auriculatum were superior as seed parents.